Implementasi Nilai Keagamaan Organisasi IPNU IPPNU di Desa Kudus melalui Kegiatan Makesta - Marsa Inayatina; Salma Zahrun Nafis; Ulya Yasmin; Muhammad Miftah (Sekolah Tinggi Ilmu Tarbiyah Al-Bukhary Labuhanbatu, 2026)
This research is motivated by the importance of strengthening Islamic and national values among students, especially amidst the challenges of the modern era that demand that the younger generation possess religious, moderate, and patriotic character. In this context, the Makesta IPNU-IPPNU activities in Kudus serve as a strategic medium for developing Nahdlatul Ulama student cadres who adhere to moderate Islamic values while upholding national values. The primary objective is to analyze how moderate Islamic values and a spirit of nationalism are integrated into the cadre development process of Nahdlatul Ulama students. The research approach used a qualitative method with field research, involving interview techniques, observation, and document collection. The results of the study indicate that Makesta activities play an effective role in instilling Islamic values such as tawasuth (middle attitude), tasamuh (tolerance), tawazun (balance), and i'tidal (justice), along with national values such as nationalism, the spirit of mutual cooperation, and social responsibility. These values are implemented through training activities, joint worship, and social actions that foster spirituality, discipline, and tolerance in participants. Theoretically, this study contributes to strengthening the study of community-based Islamic education by emphasizing the strategic function of IPNU-IPPNU in shaping a young generation with religious, nationalist, and moderate characters.